Analisis Kadar Protein Pada Beberapa Jenis Susu Tinggi Protein Dengan Metode Kjeldahl dan Spektrofotometri Visible - Syahfitri , Adelya; Daulay, Anny Sartika; Ridwanto, Ridwanto; Yuniarti , Rafita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Introduction: Protein is an essential nutrient that serves as an energy source and plays a crucial role in tissue formation. Protein deficiency can lead to various health disorders, ranging from hair loss to serious conditions such as death. High-protein milk serves as an ideal protein source as it contains essential amino acids and complete nutrients, though its consumption should be adjusted to individual needs to avoid side effects. Research Objectives: This study aims to: (1) analyze protein content in high-protein milk (Whey, Casein, and Gainer) using the Kjeldahl and Visible Spectrophotometry methods, and (2) verify the consistency between analysis results and protein content claims on product packaging. Research Methods: Analysis was conducted using two methods: the Kjeldahl method as a high-precision standard method and Visible Spectrophotometry using Biuret reagent which is more sensitive. Each sample was analyzed with six repetitions to ensure data accuracy. Samples were selected purposively based on best-selling products. Results: The results showed the highest protein content in Whey (525.87 mg/g with Kjeldahl; 873.75 mg/g with Spectrophotometry), followed by Casein (316.87 mg/g; 720.83 mg/g), and the lowest in Gainer (227.5 mg/g; 570.5 mg/g). This consistent pattern indicates conformity with packaging claims, although there were value differences between the two methods. Conclusion: The findings emphasize the importance of verifying protein content in supplement products to ensure nutritional information accuracy for consumers. The differences between the two analysis methods are presumably due to their different analytical principles. This study contributes to developing accurate protein analysis methods for high-protein milk products.